2017
DOI: 10.1111/odi.12719
|View full text |Cite
|
Sign up to set email alerts
|

Glandular odontogenic cyst: An updated analysis of 169 cases reported in the literature

Abstract: Although the recurrence rate of GOCs is not as high as previously believed, it is a relevant phenomenon (21.6%). Adjunctive procedures after enucleation should be considered. None of the clinical/radiological and histopathological features evaluated had a statistically significant effect on the recurrence rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
40
3
11

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(100 citation statements)
references
References 17 publications
3
40
3
11
Order By: Relevance
“…Chrcanovic et al did an extensive review of these 169 cases and found that these lesions were most common in males compared to females with predilection for anterior mandible. 7 In contrast to this study, our case favored female predilection and the lesion was seen in posterior mandible rather than the anterior region. Only two cases of GOCs have been previously reported from Nepal, and both cases were seen in maxilla.…”
Section: Discussioncontrasting
confidence: 91%
“…Chrcanovic et al did an extensive review of these 169 cases and found that these lesions were most common in males compared to females with predilection for anterior mandible. 7 In contrast to this study, our case favored female predilection and the lesion was seen in posterior mandible rather than the anterior region. Only two cases of GOCs have been previously reported from Nepal, and both cases were seen in maxilla.…”
Section: Discussioncontrasting
confidence: 91%
“…The aim of this study was to integrate the available published data on MNTI into an updated comprehensive comparative analysis of their clinical and radiological features, as well as the frequency of recurrence. A review of pathological lesions is important because it provides information that can improve diagnostic accuracy, allowing pathologists and surgeons to make informed decisions and refine treatment plans to optimize clinical outcomes [6][7][8][9][10] . This review revealed that MNTIs were slightly more prevalent in males and were markedly more prevalent in the maxilla, and most of the lesions were asymptomatic, presenting cortical bone perforation and tooth displacement.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the present study was to integrate the available data published in the literature on PGCG into an updated comprehensive comparative analysis of their clinical features, as well as the frequency of recurrence. A review of pathological lesions is important because it provides information that can improve diagnostic accuracy, allowing pathologists and surgeons to make informed decisions and refine treatment plans to optimize clinical outcomes …”
Section: Discussionmentioning
confidence: 99%